A Study to Assess the Factors Associated with Delay in Diagnosis of Carcinoma Breast and Carcinoma Oral Cavity among the OPD and IPD Patients at Dr. Bhim Rao Ambedkar, Institute Rotary Cancer Hospital, AIIMS, New Delhi - Singh, Vijayshree; Kumari Sharma, Kamlesh; V. S. Deo, S. (International Journal of Nursing Research, 2023)
Aim: This study aims to generate evidence on the extent and type of delay in diagnosis of carcinoma breast and oral cavity so as to provide ground for addressing the underlying issues. Materials and Methods: This quantitative descriptive study was conducted; data were collected by consecutive sampling from 60 carcinoma breast and 60 carcinoma oral cavity patients during July 2017–December 2017; using self-developed semi-structured questionnaire by interview method. All adult newly registered patients who correctly remembered their clinical history were enrolled in the study. Analysis was done using SPSS. Ethical clearance was obtained from the Institutional Ethics Committee. Primary delay is the duration between onset of symptoms till first medical contact while secondary delay is the duration between first medical contacts till final diagnosis with the help of biopsy. Results: Primary delay was 30 days (0 days–3650 days) found in 41% of subjects while secondary delay was 60 days (14 days–1095 days) present in 62.5% of subjects. The most common self-reported factor for primary delay and secondary delay was lack of awareness (45.8%) and false assurance (40%), respectively. Worsening of symptoms as reason behind seeking medical help (adjusted odds ratio [OR] 12.71; confidence interval [CI]: 3.5–45.57) and spouses of the head of family (adjusted OR 3.08; CI: 0.99–9.59) are independent predictor for primary delay. Lack of health insurance (OR 3.9; CI 1.24–12.31), negative family history of cancer (OR 2.94; CI 1.14–6.1), and false assurance given by the first medical personnel (OR 13.01; CI 4.4 38.39) are independent predictors of secondary delay. Conclusions: Significant delay was present in diagnosis. Both patient and health care workers contribute to these delays.